Tantangan Pendidikan Islam di Era Milenial - Indriani, Wiwik; Firdian, Firdian (ANWARUL, 2021)
Islamic education in the millennial era for the world of Islamic education, the millennial era holds many jobs, opportunities and challenges that must be completed and answered. One of them is that the younger generation of Islam has been exposed to the millennial effect, so that it has an impact on emerging attitudes and behaviors. The tendency and dependence on technology and communication is the most frequently seen phenomenon. Students began to spend a lot of time in front of their cell phones. Silaturrahmi, face to face and discussions are rarely seen. The emergence of this millennial era, ideally immediately responded to quickly by the world of Islamic education. The nature and purpose of Islamic education is very clear, namely to create human beings. It takes a separate strategy in realizing the goals of Islamic education in the midst of the struggles of the millennial era. Therefore, Islamic education must dare to reconstruct or reformulate its educational paradigm, so that it is able to appear and compete in the midst of the millennial wave.